Cover Image, Volume 42, Issue 4. Issue 4 (19th April 2022) - Lee, Chanju; Lee, Hyunji; Cho, Hayoon; Kim, Soyoung; Choi, Ilseob; Hwang, Young‐Sik; Jeong, Hyunju; Jang, Hogi; Pak, Sehyun; Hwang, Deok‐Sang; Han, Ik‐Hwan; Bae, Hyunsu
Abstract : The cover image is based on the Letter to Editor Combination of anti‐PD‐L1 antibody with peptide MELdKLA targeting M2 tumor‐associated macrophages suppresses breast cancer metastasis by Hyunsu Bae et al., https://doi.org/10.1002/cac2.12276 .